Wild food plants and fungi sold in the markets of Luang Prabang, Lao PDR - Łukasz Łuczaj; Vichith Lamxay; Khamphart Tongchan; Kosonh Xayphakatsa; Kongchay Phimmakong; Somphavanh Radavanh; Villapone Kanyasone; Marcin Pietras; Małgorzata Karbarz (BMC, 2021)
Abstract Background Open air markets hold an important position for ethnobiologists. In Southeast Asia, they are seriously understudied, in spite of their incredible biocultural diversity. In order to fill this gap we recorded plants and fungi sold in the open air markets of Luang Prabang, Lao PDR. Methods The markets were visited 38 times in four seasons: the dry season, early monsoon, mid-monsoon, and end-of-monsoon, at least 8 times per season. All items were photographed and voucher specimens were collected. Fungi were identified using DNA barcoding techniques. Results We recorded 110 species of wild edible plants and 54 species of fungi, including 49 wild-collected species. The sold plants included 86 species of green vegetables, 18 species of fruits and 3 species of flowers. Products from woody species constitute around half of all taxa sold. These include the young shoots of tree leaves, which are used for salads-an interesting feature of Lao cuisine. A large number of extremely rare Russula, with no reference sequences represented in databases or even species unknown to science is present on sale in the markets. Conclusions Luang Prabang markets are some of the richest in species of wild edible plants and fungi in Asia, and indeed in the whole world. It is worth pointing out the exceptionally long list of wild edible mushrooms which are sold in Luang Prabang (and probably elsewhere in Laos). We view the Morning Market of Luang Prabang as a cultural treasure that unites the traditions of eating a large number of living species with very diverse flora and fauna. Measures should be taken to strike a balance between local foraging traditions and nature conservation priorities.